2023
DOI: 10.3390/nu15020419
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Dietary Inflammatory Index and Sleep Metrics in the Energy Balance Study (EBS)

Abstract: (1) Background: Sleep, a physiological necessity, has strong inflammatory underpinnings. Diet is a strong moderator of systemic inflammation. This study explored the associations between the Dietary Inflammatory Index (DII®) and sleep duration, timing, and quality from the Energy Balance Study (EBS). (2) Methods: The EBS (n = 427) prospectively explored energy intake, expenditure, and body composition. Sleep was measured using BodyMedia’s SenseWear® armband. DII scores were calculated from three unannounced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Seven studies assessed the association between sleep duration and dietary inflammation using the DII. Three studies assessed sleep duration by using objective methods (i.e., using actigraphy) [ 24 , 26 , 29 ]. Four studies assessed sleep duration subjectively using either the Pittsburgh Sleep Quality Index (PSQI) [ 19 , 20 , 33 ] or self-reported hours of sleep per night [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies assessed the association between sleep duration and dietary inflammation using the DII. Three studies assessed sleep duration by using objective methods (i.e., using actigraphy) [ 24 , 26 , 29 ]. Four studies assessed sleep duration subjectively using either the Pittsburgh Sleep Quality Index (PSQI) [ 19 , 20 , 33 ] or self-reported hours of sleep per night [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were conducted in healthy adults across the lifespan [ 19 , 20 , 21 , 24 , 26 , 29 , 33 ]. Of these, two reported outcomes in younger participants [ 26 , 33 ], while four studies focused on middle-aged participants [ 19 , 20 , 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 43 Still, these findings are consistent with the results of previous longitudinal studies, in which an increase in the DII was associated with longer, objectively measured, wake-after-sleep-onset (WASO) among European American obese and overweight pregnant women, police officers, and young adults from the United States. 18 19 46 47 Additionally, an increase in DII was associated with a decrease in sleep efficiency. 46 47 However, in the present study, we also found an unforeseen result that links higher E-DIIs with a reduced risk of daytime dysfunction, with individuals in the third E-DII quartile having less daytime dysfunction compared with those in the first E-DII quartile.…”
Section: Discussionmentioning
confidence: 98%
“…18 19 46 47 Additionally, an increase in DII was associated with a decrease in sleep efficiency. 46 47 However, in the present study, we also found an unforeseen result that links higher E-DIIs with a reduced risk of daytime dysfunction, with individuals in the third E-DII quartile having less daytime dysfunction compared with those in the first E-DII quartile. This result also contradicts those of the study by Masaad et al, 17 who found that high E-DIIs are positively associated with daytime dysfunction.…”
Section: Discussionmentioning
confidence: 98%